Analisis Struktural Puisi “Walau” Karya Soetardji Calzoum Bachri - Listia Rizkiyani; Alif Abdur Rafi Deriansyah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Literary works are natural works created from human reason and desire, not without reason if literary works that are born are closely related to study and appreciation. One of the literary works that contains the author's thoughts and problems that occur in life is poetry. Poetry studies can be done from various aspects, one of which is through a structural approach. This study contains an analysis of the poem